One-dimensional anodic TiO2 nanotubes coated by atomic layer deposition: Towards advanced applications. (March 2019) - Dvorak, Filip; Zazpe, Raul; Krbal, Milos; Sopha, Hanna; Prikryl, Jan; Ng, Siowwoon; Hromadko, Ludek; Bures, Filip; Macak, Jan M.
Graphical abstract: Highlights: Atomic layer deposition (ALD) allows to uniformly coat surfaces by various materials. Coating of high aspect ratio porous nanostructures is very attractive for applications. The use of ALD for functionalization of anodic TiO2 nanotube (TNT) layers is reviewed. Properties of TNT layers are strongly enhanced by coatings of various compositions. Many different applications of the composite structures are presented and discussed. Abstract: Atomic layer deposition (ALD) represents a unique deposition technique that allows to coat uniformly various high aspect ratio (HAR) porous nanostructures, in addition to its traditional role to coat flat substrates (e.g. Si wafers). Self-organized anodic TiO2 nanotube (TNT) layers belong among the most investigated inorganic nanostructures. They possess highly functional materials with promising application potential across many technological fields. Herein, we review the utilization of ALD for the functionalization of anodic TNT layers by secondary materials to advance their physicochemical and photoelectrochemical properties. First, the application of ALD for functionalization of porous aluminium oxide, which represent fundamental HAR nanostructure, is briefly introduced. Then the main experimental parameters governing the uniformity and the conformality of ALD coating within HAR nanostructures are discussed. Finally, the review focuses on the use of ALD to deposit secondary materials into TNT layers for various purposes — the introduction of pioneering studies is followed by particular examples of ALD based functionalizations of coated TNT layers for optimized visible-light absorption, charge separation and passivation, (photo)catalysis, stability, gas sensing, and energy storage.